Assessing human well‐being constructs with environmental and equity aspects: A review of the landscape - Betley, Erin C.; Sigouin, Amanda; Pascua, Pua’ala; Cheng, Samantha H.; MacDonald, Kenneth Iain; Arengo, Felicity; Aumeeruddy‐Thomas, Yildiz; Caillon, Sophie; Isaac, Marney E.; Jupiter, Stacy D.; Mawyer, Alexander; Mejia, Manuel; et al. (People and nature (Hoboken, N.J.), 2023)
Decades of theory and scholarship on the concept of human well‐being have informed a proliferation of approaches to assess well‐being and support public policy aimed at sustainability and improving quality of life. Human well‐being is multidimensional, and well‐being emerges when the dimensions and interrelationships interact as a system. In this paper, we illuminate two crucial components of well‐being that are often excluded from policy because of their relative difficulty to measure and manage: equity and interrelationships between humans and the environment. We use a mixed‐methods approach to review and summarize progress to date in developing well‐being constructs (including frameworks and methods) that address these two components. Well‐being frameworks that do not consider the environment, or interrelationships between people and their environment, are not truly measuring well‐being in all its dimensions. Use of equity lenses to assess well‐being frameworks aligns with increasing efforts to more holistically characterize well‐being and to guide sustainability management in ethical and equitable ways. Based on the findings of our review, we identify several pathways forward for the development and implementation of well‐being frameworks that can inform efforts to leverage well‐being for public policy. Résumé Des décennies de théorie et de recherche sur le concept de bien‐être humain ont généré une prolifération d'approches pour évaluer le bien‐être et encourager les décideurs à intégrer la durabilité et l'amélioration de la qualité de vie dans leurs politiques publiques. Le bien‐être humain est multidimensionnel; il est favorisé par l’interaction entre ses multiples dimensions qui constituent un système. Dans cet article, nous soulignons deux composantes cruciales du bien‐être qui sont souvent exclues des politiques publiques en raison de leur relative difficulté à mesurer et à gérer: l'équité et les relations entre les humains et l’environnement. Nous utilisons des méthodes mixtes pour inventorier et résumer les progrès réalisés à ce jour dans le développement et l’application des cadres conceptuels du bien‐être (y compris des cadres d’analyse et des méthodes) qui traitent de ces deux composantes. Les cadres d’analyse sur le bien‐être qui ne tiennent pas compte de l'environnement ou des relations entre les humains et l’environnement, ne mesurent pas le bien‐être dans toutes ses dimensions. L’adoption de l’équité dans les méthodes d’évaluation du bien‐être, permet de caractériser plus holistiquement la notion de bien‐être et ainsi de développer une approche de la durabilité plus éthique et équitable. Sur la base des résultats de notre recherche bibliographique, nous identifions plusieurs voies pour développer et opérationnaliser des cadres de travail favorisant l’intégration du bien‐être dans les politiques publiques. Resumen Décadas de teoría y estudios sobre el concepto de bienestar humano han informado una proliferación de enfoques para evaluar el bienestar y apoyar la política pública orientada a la sustentabilidad y mejora de la calidad de vida. El bienestar humano es multidimensional y el bienestar surge cuando las dimensiones e interrelaciones interactúan como un sistema. En este trabajo, iluminamos dos componentes fundamentales del bienestar que frecuentemente son excluidos de políticas debido a su relativa dificultad para medir y gestionar: la equidad y las interrelaciones entre las personas y el medio ambiente. Usamos métodos mixtos para revisar y resumir el progreso hasta la fecha en el desarrollo de construcciones de bienestar (incluyendo marcos y métodos) que abordan estos dos componentes. Estructuras de bienestar que no consideran el medio ambiente, o interrelaciones entre las personas y su entorno, no están midiendo el bienestar en todas sus dimensiones. El uso de enfoques de equidad para evaluar los marcos de bienestar es consistente con el aumento en esfuerzos para caracterizar más holísticamente el bienestar y para orientar la gestión de la sustentabilidad de forma ética y equitativa. Basándonos en los hallazgos de nuestra revisión, identificamos varias vías para el desarrollo e implementación de marcos de bienestar que pueden informar iniciativas que aprovechan el bienestar para políticas públicas. A free Plain Language Summary can be found within the Supporting Information of this article. A free Plain Language Summary can be found within the Supporting Information of this article.